ARTS-BASED PEDAGOGY FOR CHARACTER EDUCATION: A QUALITATIVE CASE STUDY OF NATIONALISM AND SOCIAL SKILL DEVELOPMENT IN PRIMARY SCHOOLS - Fathul Jannah; Aldy Ferdiyansyah; Noorhapizah Noorhapizah; Akhmad Riandy Agusta; Yuliasari Yuliasari; Muhammad Ahyat Rahliannor (Universitas Labuhanbatu, 2026)
Purpose – This study examines the implementation of arts-based pedagogy, integrating role-play and traditional dance into primary school learning, to explore how students experience and internalize national values and social skills through participatory cultural activities.Methodology – This study employed a qualitative case study design at SDN Belitung Selatan 2, involving 30 primary school students selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using thematic analysis to identify recurring patterns and meanings related to students’ learning experiences.Findings – The findings revealed five major themes: active student engagement in participatory learning, increased self-confidence through expressive experiences, strengthened social skills through collaborative interaction, internalization of nationalism values through cultural representation, and the formation of meaningful learning through integrated experiences. Role-play and traditional dance encouraged students to participate more actively, communicate and collaborate with peers, express themselves confidently, and understand values such as cooperation, togetherness, and cultural identity through direct experience. These findings indicate that arts-based pedagogy supports cognitive, affective, and social development by creating participatory and culturally contextual learning environments. The study suggests that integrating the arts and local culture into classroom instruction can foster more meaningful, character-oriented learning in primary education.Contribution –The study also offers practical implications for teachers seeking to design more collaborative, culturally contextual, and experience-based learning environments that integrate cognitive, affective, and social dimensions simultaneously.